Akreditasi Perpustakaan Bentuk Penguatan Pondasi Perguruan Tinggi Berbasis Teknologi Informasi - Merdansah Merdansah (AL Maktabah, 2017)
The important role of the library is demanded to support the accreditation and basic needs of the university. In addition, technological developments change people's behavior in searching and utilizing information. Many communities have been overcome by developing university libraries that are oriented to the academic community and the development of information technology. The steps are performed with (a). Determine the direction of development, (b). Standardization of resources, (c).Development of information systems, and (d).evaluation. The effort is a strong foundation of the foundation of the library to the international library that melanasi strengthening of the foundation of universities based on information technology.